The answer is 16 ok its going to help mabye
Answer:
It equals x/z.
Step-by-step explanation:
Hope this helps!!!!
oh ok alr thank you so much
Answer:
c. (x^2+1)(x^2+a)-a = x^2(x^2+a+1)
Step-by-step explanation:
You can use FOIL or the distributive property to expand the product of binomials, Then collect terms and factor out the common factor.
(x^2+1)(x^2+a)-a
= x^2(x^2 +a) +1(x^2 +a) -a
= x^4 +ax^2 +x^2 +a -a
= x^4 +ax^2 +x^2
= x^2(x^2 +a +1) . . . . . matches choice C
6-4(2/3)
5(3/3)-4(2/3)
1(1/3)